Juridical Review of the Arrangement of Duties and Functions of the Tolitoli Regency KPU Secretariat in the Implementation of General Elections According to Law Number 7 of 2017 - Warda Said (PT FORMOSA CENDEKIA GLOBAL, 2023)
KPU is an institution that holds the mandate of the 1945 Constitution as Election Organizer in Indonesia. In carrying out its duties and functions, the KPU is assisted by the KPU Secretariat, which in holding elections the two internal elements of this institution must run well even though their backgrounds are different, each of which is hierarchical from the center to the regions. The purpose of this writing is to find out the legal arrangements of the two internal institutional elements between the Tolitoli Regency KPU Membership and the Tolitoli Regency KPU Secretariat in the success of the General Election. The method used is the normative legal method and from the collected data, it will then be identified for further processing and qualitative analysis. The results obtained from the results of this study show that the relationship arrangements between KPU Membership and the KPU Secretariat at the district/city level are a coordinative relationship within one election management institution